Intranasal Delivery of Temozolomide-Conjugated Gold Nanoparticles Functionalized with Anti-EphA3 for Glioblastoma Targeting - Wang, Liangxiao; Tang, Shengnan; Yu, Yawen; Lv, Yanan; Wang, Aiping; Yan, Xiuju; Li, Nuannuan; Sha, Chunjie; Sun, Kaoxiang; Li, Youxin (Molecular pharmaceutics, 2021)
Glioblastoma multiforme (GBM) is a highly lethal and aggressive tumor of the brain that carries a poor prognosis. Temozolomide (TMZ) has been widely used as a first-line treatment for GBM. However, poor brain targeting, side effects, and drug resistance limit its application for the treatment of GBM. We designed a Temozolomide-conjugated gold nanoparticle functionalized with an antibody against the ephrin type-A receptor 3 (anti-EphA3-TMZ@GNPs) for targeted GBM therapy via intranasal administration. The system can bypass the blood-brain barrier and target active glioma cells to improve the glioma targeting of TMZ and enhance the treatment efficacy, while reducing the peripheral toxicity and drug resistance. The prepared anti-EphA3-TMZ@GNPs were 46.12 ± 2.0 nm and suitable for intranasal administration, which demonstrated high safety to the nasal mucosa in a toxicity assay. In vitro studies showed that anti-EphA3-TMZ@GNPs exhibited significantly enhanced cellular uptake and toxicity, and a higher cell apoptosis ratio has been seen compared with that of TMZ (54.9 and 14.1%, respectively) toward glioma cells (C6). The results from experiments on TMZ-resistant glioma cells (T98G) demonstrated that the IC of anti-EphA3-TMZ@GNPs (64.06 ± 0.16 μM) was 18.5-fold lower than that of TMZ. In addition, Western blot analysis also revealed that anti-EphA3-TMZ@GNPs effectively down-modulated expression of O -methylguanine-DNA methyltransferase and increased chemosensitivity of T98G to TMZ. The antiglioma efficacy in vivo was investigated in orthotopic glioma-bearing rats, and the results demonstrated that the anti-EphA3-TMZ@GNPs prolonged the median survival time to 42 days and increased tumor-cell apoptosis dramatically compared with TMZ. In conclusion, anti-EphA3-TMZ@GNPs could serve as an intranasal drug delivery system for efficacious treatment of GBM.